FINANCIAL LITERACY AND MARKETING DIGITALIZATION GUIDANCE FOR ALFI MEAT GRINDING UMKM IN PINRANG REGENCY - jumriah basri; A. Kartini Sari Putri D; Ari Ayu; Auliyah Nurwafiyyah; Muhammad G. Try Heady; Andi Sri Kumala Putri (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
The main objective of this community service activity is to improve financial literacy and optimize digital marketing for the Alfi Meat Grinding MSME in Pinrang Regency. The implementation method involves intensive mentoring for the owner and workforce through systematic bookkeeping education and digital-based promotion techniques. The results show a significant transformation, where the business actor now understands the urgency of separating business and personal finances as the foundation for sound business management. The establishment of a neat, simple bookkeeping system allows for better cash flow transparency for operations. Increased awareness in utilizing social media as a promotional channel has proven effective in expanding market reach. Through this continuous mentoring, the Alfi Meat Grinding MSME is expected to achieve economic independence, improve competitiveness in an increasingly competitive market, and make a positive contribution to the stability and growth of the creative economy in the Pinrang Regency area in a sustainable and measurable way for the improvement of local community welfare.